Early disruptions in vitamin D receptor signaling induces persistent developmental behavior deficits in zebrafish larvae - Barnes, Morgan; Burton, Derek; Marsden, Kurt; Kullman, Seth W. (PLOS ONE, 2025)
A critical function of the nervous system is to rapidly process sensory information and initiate appropriate behavioral responses. Defects in sensory processing and behavior selection are commonly observed in neuro-psychiatric conditions including anxiety, autism (ASD), and schizophrenia. The etiology of sensory processing disorders remains equivocal; however, it is hypothesized that extrinsic environmental factors can play fundamental roles. In this study we examine the importance of vitamin D (1α, 25-dihydroxyvitamin D3) receptor signaling during early life stage development on sensory processing and neurobehavioral health outcomes. While vitamin D has traditionally been associated with mineral ion homeostasis, accumulating evidence suggests non-calcemic roles for vitamin D including early neurodevelopment. Here we demonstrate that systemic disruption of vitamin D receptor (VDR) signaling with a conditional dominant negative (dnVDR) transgenic zebrafish line results in specific visual and acoustic sensorimotor behavior defects. Induction of dnVDR between 24–72 hours post fertilization (hpf) resulted in modulation of visual motor response with demonstrated attenuation in acute activity and hypolocomotion across multiple swimming metrics when assayed at 6- and 28-days post fertilization (dpf). Disruption in VDR signaling additionally resulted in a strong and specific attenuation of the Long-Latency C-bends (LLC) within the acoustic startle response at 6 dpf while Short-Latency C-bends (SLC) were moderately impacted. Pre-pulse inhibition (PPI) was not impacted in young larvae, however young adult fish exhibited a significantly attenuated PPI at 28 dpf suggesting an inability to properly modulate their startle responses and persistent effects of VDR modulation during early development. Overall, our data demonstrate that modulation of vitamin D signaling during critical windows of development irreversibly disrupts the development of neuronal circuitry associated with sensory processing behaviors which may have significant implications to neurobehavioral health outcomes.